OC-072 Does endoscopic duodenal-jejunal exclusion improve non-alcoholic fatty liver disease (nafld) in patients with diabesity?. (22nd June 2015) - Gupta, P Sen; Bajwa, RS; Roy, AA; Butler, D; Ashmore, J; Lee, SI; Murray, L; McGowan, B; Drummond, RS; Hayee, B; Amiel, SA; Ryder, RE
Abstract : Introduction: The rapidly increasing global prevalence of NAFLD paralleling the diabesity pandemic demands that new effective therapies are identified. The aim of this study was to investigate the impact of an endoscopic duodenal-jejunal liner (DJL) (endobarrier) with or without glucagon-like peptide-1 receptor agonist (GLP-1RA) therapy on NAFLD. Method: Adults with type 2 diabetes and obesity despite GLP-1RA therapy (HbA1c ≥7.5%, BMI ≥35 kg/m 2 ) were randomised to (1) DJL+GLP1RA (liraglutide 1.2 mg daily) therapy; (2) DJL alone; (3) escalated dose liraglutide (1.8 mg daily). Descriptive statistics were performed (%frequency, mean ±SD, median (IQR)). Changes in weight, HbA1c (paired t-test) and non-invasive composite scores (NAFLD fibrosis score (NFS) and AST to platelet ratio index (APRI) score) were calculated over 3 months within groups (Wilcoxon test). A sub-group underwent magnetic resonance imaging (MRI) to evaluate hepatic fat fraction over 4 months of DJL implant (paired t-test). Hepatic fat fraction (HFF) was calculated by comparing the in-phase/ out-of-phase signal by 3 blinded independent assessors using 3 regions of interest in the liver. Results: Of 40 patients (age 51.2 ± 10.0 years, 40.0% male, 60.0% Caucasian, baseline BMI 41.4 ± 4.9 kg/m 2, HbA1c 78 ± 16 mmol/mol (9.3 ± 1.4%)), baseline ALT was 27 (17.8–41.0) IU/l, AST 21 (17.8–41.5) IU/l, ƔGT 35 (22.0–71.5) IU/l and 82.5% had a NFS regarded as at intermediate (65.0%) or high risk (17.5%) for fibrosis. Over 3 months, there was a reduction in weight by 7.3 ± 4.0 kg and in HbA1c by 14.5 ± 15.3 mmol/mol (1.3 ± 1.4%), P < 0.0001. NFS reduced by 0.36 (–0.1 to 1.0), n = 15, P = 0.04; 0.7 (0.2 to 1.6), n = 14, P = 0.003; 0.2 (–0.1 to 0.8), n = 11, P = 0.14 in groups 1, 2 and 3 respectively. APRI fell by 0.08 (0.04 to 0.14), P = 0.02 but was not significantly altered in groups 1 or 3. Of 5 patients undergoing MRI, baseline HFF fell from 16.2 ± 10.4% to 3.5 ± 5.6% at 4 months post-DJL (% reduction of 82.1 ± 24.4%, P = 0.028). Conclusion: There was a high prevalence of NAFLD in this group of patients with diabesity. Despite previous suboptimal response to GLP1RA therapy there was improvement in NFS and APRI scores in those treated with DJL+GLP1RA and DJL alone, the latter group demonstrating a superior response. Implantation of DJL was effective at reducing HFF. These data suggest duodenal exclusion may be an effective future therapy for NAFLD. Disclosure of interest: None Declared.